The Determinants of Chronic Bronchitis in Aboriginal Children and Youth - Alomgir Hossain; Stephanie Konrad; James A Dosman; Ambikaipakan Senthilselvan; Jesse McCrosky; Punam Pahwa (Canadian Respiratory Journal)
BACKGROUND: There is limited knowledge concerning chronic bronchitis (CB) in Canadian Aboriginal peoples.